2D Dual Anisotropic Conductive Janus Nanostrips Array Pellicle and Derivative 3D Janus‐structural Pipe Concurrently Endowed with Magnetism and Red‐green Two‐colored Fluorescence. Issue 12 (10th November 2020) - Yang, Xiuling; Qi, Haina; Tian, Jiao; Xie, Yunrui; Sheng, Yuqi; Dong, Xiangting; Ma, Qianli; Liu, Guixia; Wang, Jinxian; Yu, Wensheng
Abstract: 2D dual anisotropic conductive left‐to‐right structured special Janus array pellicle (SJAP) synchronously functionalized by red‐green two‐colored fluorescence and magnetism was constructed by electrospinning. SJAP is assembled by two closely joint films, viz. {[CoFe2 O4 /polymethylmethacrylate (PMMA)]@[polyaniline (PANI)/PMMA]}//[Tb(acac)3 bipy/PMMA] special Janus nanostrip array film as left‐side (L‐SJAF) and {[CoFe2 O4 /PMMA]@[PANI/PMMA]}//[Eu(TTA)3 (TPPO)2 /PMMA] special Janus nanostrip array film as right‐side (R‐SJAF). Microscopically, Janus nanostrip with coaxial//monaxial structure effectively limits three functional substances to their own regions, avoiding adverse impact among conduction, magnetism and fluorescence to achieve enhanced fluorescence and strong anisotropic conduction. Macroscopically, SJAP realizes the division of green and red fluorescence regions, and close binding of L‐SJAF and R‐SJAF with single anisotropy enables SJAP to obtain dual anisotropic conduction. The high integration of micro and macro portion endues SJAP with dual anisotropic conduction, magnetism and red‐green two‐colored fluorescence. Two types of 3D Janus‐structural pipe were created by curling SJAP, achieving the structural evolution from 1D nanostrip to 2D SJAP then to 3D pipe. The new 3D pipes exhibit identical properties with SJAP. The novel SJAP and 3D pipe have wide prospect in electronic skin. This design theory and technology provide an idea to prepare other polyfunctional materials. Abstract : 2D dual anisotropic conductive left‐to‐right structured special Janus nanostrips array pellicle (SJAP) are prepared by using Janus nanostrip with concentric//monaxial structure as construction unit via electrospinning. 2D SJAP possesses red‐green two‐colored fluorescence, dual anisotropic conduction and magnetism. Two types of 3D Janus‐structural pipe are obtained by crimping 2D SJAP and exhibit the same polyfunctionalities as 2D SJAP. In 2D SJAP and 3D Janus‐structural pipe, macro‐ and micro‐partition are simultaneously actualized to reduce adverse interactions among various materials to acquire excellent multifunctionalities.